2022
DOI: 10.1007/s00181-021-02183-4
|View full text |Cite
|
Sign up to set email alerts
|

On directors’ compensation: a multilevel analysis of Spanish listed companies

Abstract: This study analyzes the determinants of the annual compensation of directors belonging to the boards of the Spanish companies that constitute the IBEX 35 stock index. We investigate the importance of observed and unobserved heterogeneity in explaining director compensation. Based on a three-level mixed effect model, our analysis includes time-invariant random effects at company and manager level as determinants of director pay. We find that company effects explain 30% of the variation in director pay, while co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…For example, (Carretta et al 2006;Marchetti and Stefanelli 2009;Mallin et al 2015;Goh and Gupta 2016;Fedaseyeu et al 2018) found that age is significantly positively related to compensation, but with a small economic magnitude. Núñez et al (2022) also found that the age of the director has a positive effect on the compensation level up to 58 years, thereafter, the relationship turns negative. Thus, I expect RCC's age to be positively associated with their remuneration.…”
Section: H2mentioning
confidence: 84%
See 3 more Smart Citations
“…For example, (Carretta et al 2006;Marchetti and Stefanelli 2009;Mallin et al 2015;Goh and Gupta 2016;Fedaseyeu et al 2018) found that age is significantly positively related to compensation, but with a small economic magnitude. Núñez et al (2022) also found that the age of the director has a positive effect on the compensation level up to 58 years, thereafter, the relationship turns negative. Thus, I expect RCC's age to be positively associated with their remuneration.…”
Section: H2mentioning
confidence: 84%
“…Fedaseyeu et al (2018) found that the outside directors' remuneration was tied to the skills and experiences for a large sample of US-listed firms (1777 firm-year observations; 13,239 director-year observations) between 2006 and 2010; their results showed that more qualified directors perform more board functions and thus receive higher pay. Núñez et al (2022) found that professional and personal attributes were the main determinants of directors' compensation for Spanish-listed companies IBEX 35 (1458 firm-year observations; 531 director-year observations) during the period 2015-2017 (in terms of the position category on the board, gender, age talent attributes, and the seniority in the company on the board).…”
Section: Non-executive Directors' Remunerationmentioning
confidence: 99%
See 2 more Smart Citations
“…compensation depends mainly on rm-level variables, while executive directors' compensation depends more on director-level variables Nuñez et al (2022). obtains that the effect of the company and director characteristics taken together explain 77% of the compensation of directors belonging to the Spanish Ibex-35 stock index and that there are some random effects that separate some directors from the expected remuneration derived from the xed part of the model.…”
mentioning
confidence: 92%